Parametric Uncertainty Analysis of Inverse Linear Electric Circuit Problems - Borquez-Berenguer, J; Acosta-Barbosa, K (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper focus on the robustness analysis inverse problem of linear electric circuits. The aim is to determine what amount of variations of the input parameters can an electrical or electronic system tolerate, such that the output variables (e.g. conducted noise) does not exceed an upper bound in the frequency domain. Based on the well-known theory of robust control and convex optimization, we propose a procedure to check which commercial values of tolerance can be picked for components of an arbitrary electric circuit, while guaranteeing a prescribed upper bound. The proposed method is applied to an op-amp active band-pass filter and the results are analyzed and discussed. © 2017 IEEE.
Keywords: Convex Optimization; Inverse Problem; Uncertainty Analysis; Worst-case Analysis